Digital Devices: Blessings or Curses to University Students’ Learning Effectiveness in the Classroom - Omotayo Adewale Awodiji; Brenda Baluka (Studies in Learning and Teaching, 2023)
Students' use of digital devices (DDs) and the disruption of their attention in class are generally considered causes for considerable concern regarding how they affect their performance in the classroom. Based on students' perceptions, this study aims to determine whether these DDs positively impact learning effectiveness. Using a qualitative exploratory design, the study sought to better understand the subject matter under investigation through the students' experiences. Before submission of the data to software for analysis, another person reviewed the transcribed text independently. ATLAS.ti version 22 software was used by an independent analyst to analyse the data. Findings showed that personal computers, tablets, mobile phones, and iPads are classrooms’ most commonly used DDs. Even though the advantages of using DDs in the classroom are significant, it was suggested that appropriate and responsible use of DDs is crucial for students to develop digital literacy, online safety, and responsible technology use habits. Teachers and schools should establish guidelines and provide digital citizenship education. The study concludes that teachers need to implement strategies that minimise distractions while helping students.